Accurate, precise, simultaneous myocardial T1 and T2 mapping using a radial sequence with inversion recovery and T2 preparation. (28th August 2019) - Shao, Jiaxin; Zhou, Ziwu; Nguyen, Kim‐Lien; Finn, J. Paul; Hu, Peng
Abstract: We propose a simultaneous myocardial T1 and T2 mapping technique using a radial sequence with inversion recovery and T2 preparation, which achieves high accuracy and precision, with T1 and T2 reproducibility similar to the Modified Look‐Locker Inversion recovery (MOLLI) sequence and the conventional bright blood T2 mapping technique, respectively. The sequence was developed by incorporating gold angle radial fast low angle shot (FLASH) readout combined with an inversion pulse and T2prep pulses. The extended Bloch equation simulation with slice profile correction (BLESSPC) algorithm was proposed to reconstruct T1 and T2 maps at the same time in a few seconds, while maintaining good T1 and T2 estimation accuracy. Accuracy and precision were compared among the proposed technique, MOLLI and conventional T2 mapping techniques using phantom studies, 10 healthy volunteers and three patients. In phantom studies, the proposed technique was more accurate than MOLLI ( P  < 0.05) while achieving similar precision ( P  = 0.3) in T1 estimation, and was more accurate ( P  < 0.05) and precise ( P  < 0.001) than conventional T2 mapping (two‐parameter fitting) in T2 estimation. In vivo, the proposed technique achieved significantly higher T1 values ( P  < 0.001) and similar reproducibility ( P  = 0.3) compared with MOLLI, with significantly lower T2 values ( P  < 0.001) and similar reproducibility ( P  = 0.6) compared with the conventional T2 mapping technique. Thus, the proposed radial T1‐T2 mapping technique allows for accurate, precise, simultaneous myocardial T1 and T2 mapping in an 11‐heartbeat single breath‐hold acquisition. Abstract : We propose a simultaneous myocardial T1 and T2 mapping technique using a radial sequence with inversion recovery and T2 preparation in a single breath‐hold of 11 heartbeats. For T1 and T2 estimation, the proposed technique achieved reproducibility comparable with the reference sequence, MOLLI T1, and conventional T2 mapping techniques, while reducing scan time and exhibiting better accuracy without heart rate dependence.